A Case of Actinomycetoma Treated with Trimethoprim + Sulfamethoxazole - Subekcha Karki; Ma Luisa Abad-Venida (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
A 32-year-old man presented with a history of progressive, painful nodular growths with discharge consisting granules over the right thigh, inguinal area and right foot. Histopathological examination of the tissue biopsy was actinomycotic mycetoma. The patient showed improvement with trimethoprimsulfamethoxazole.The novelty of our case is to use Co-trimoxazole as a first line treatment modality for cases diagnosed or suspected as actinomycetoma.